Thermal activation of ordinary Portland cement-slag mortars - Sajedi, Fathollah; Razak, Hashim Abdul (Elsevier, 2010)
Thirty one mix proportions of ordinary Portland cement (OPC)-slag mortars (OSM) used to study the effects of temperature on early and ultimate strengths. Three levels of slag (0, 40, and 50) and different temperatures were used; it was found that 50 is the optimum level and 60Â°C with 20. h duration is also optimum. The maximum strengths obtained of optimum mortar, at 3 and 7. days, for specimens cured in the air, are 55.00 and 62.00. MPa, respectively. These strength levels are 64.50 and 66.50 greater than those without heating. The results show for 0 and 2. h heating time, the strength of specimens cured in the water are greater than those cured in the air, but for 4-26. h, this statement is reversed. This is a novelty, is very important in the precast industry and has many advantages for arid regions to overcome curing of concrete structures.